Some Indo-European Archetypes as Ground for Philosophical and Mythological Thinking - Beresnevičius, Gintaras (Problemos, 1990)
The article deals with the problem of mythological thinking and its philosophical interpretation in Greek world on the one side and with the Baltic world outlook as formed by basic Indo-European productive archetypes on the other side. The early European philosophy presents by itself not the “demythologisation” of the world, but rather some kind of the hermeneutics Indo-European productive archetypes. The Baltic mythology is also based on the same archetypes, and deeper insight into the Baltic art and folklore makes it possible to differentiate the common ground for the many specific forms of Indo-European thinking.